Negotiation Text Writing Training With A Differentiated Approach For Grade XI Students UNP Laboratory Development High School - Tatalia, Ricci Gemarni; Nisja, Indriani (Bhandar: Harvesting Community Service in Asia, 2024)
This community service aims to help students become skilled at writing negotiation texts. This activity was carried out at UNP Laboratory Development High School. The implementation of learning to write negotiation texts in Community Service applies learning with a differentiated approach. Efforts are made to implement differentiated learning by paying attention to learning activities that can accommodate students according to their needs and learning styles. The method used in Community Service is a learning method with the application of differentiated learning. Learning differentiates learning pressure according to students' learning styles, namely visual, auditory, and kinesthetic. The results of the service implementation show that students in the auditory, visual, and kinesthetic learning groups can follow the learning process well. Negotiation text learning activities became interesting, students were actively involved, and the results of students' negotiation text writing skills showed an average score of 84 at a mastery level of 76-85% in the Good category.